Analisis Academic Burnout pada Siswa di Sekolah Menengah Pertama Negeri 6 Takengon dan Peran Guru Bimbingan dan Konseling dalam Mengurangi Kejenuhan Belajar - Syarifah Ainy Rambe; paun paun; Faris Wasim (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2026)
This research aims to analyze academic burnout among students at SMP Negeri 6 Takengon and the role of Guidance and Counseling (BK) teachers in reducing learning saturation. The research uses a qualitative approach with descriptive type. Research subjects consist of students experiencing academic burnout, BK teachers, and homeroom teachers selected using purposive sampling technique. Data collection techniques were conducted through observation, in-depth interviews, and documentation. Data analysis uses the interactive model of Miles and Huberman. Results show that academic burnout is characterized by emotional exhaustion, decreased learning motivation, and apathetic attitude towards learning. Causal factors include high task load, academic pressure, and lack of variation in learning methods. The role of BK teachers is carried out through individual counseling services, group guidance, and provision of learning motivation. Keywords: academic burnout, students, guidance and counseling teachers, learning boredom, individual counseling, group guidance